HUBUNGAN HASIL BELAJAR MATA PELAJARAN MATEMATIKA DAN FISIKA DENGAN PENGETAHUAN SISWA PADA MATA PELAJARAN PEMPROGRAMAN DASAR DI SMK NEGERI 7 TAKALAR - Dian Atmasani; Muhammad Yahya; Muhammad Farid (Program Studi S2 Pendidikan Teknologi dan Kejuruan, 2021)
This study aims to determine the description of student learning outcomes in Mathematics, Physics and Basic Programming subjects at SMK Negeri 7 Takalar and to determine the relationship between student learning outcomes in Mathematics and Physics subjects with Student Knowledge in Basic Programming subjects. Ex-post facto research method. The total population is 210 people and the sample is 63 people taken at random proportionally. Data collection using documentation and tests. Hypothesis testing is carried out after conducting the analysis prerequisite test. The results of this study indicate that: (1) student learning outcomes in Mathematics are in the